Flora of Espírito Santo: Barnebyoid and Bunchosioid clades (Malpighiaceae) - Barros,Paulo Henrique Dettmann (2022)
Abstract We present the taxonomic treatment of four genera and six Malpighiaceae species from the state of Espírito Santo, Brazil. We analyzed herbarium specimens (BHCB, CRVD, MBML, RB, SPF and VIES) and collected specimens in field expeditions from January 2018 to April 2019. Bunchosia was the richest genus with three species recorded in this state, followed by Barnebya, Heladena, and Thryallis, with a single species each. We present morphological descriptions, identification keys, taxonomic notes, distribution maps, and photographic plates for all species.